Pengungkapan Lingkungan, Sosial, dan Tata Kelola terhadap Kinerja Perusahaan Perbankan Indonesia diproksikan dengan Profitabilitas - Dimas Budiman Sujatmiko; Yusron Difinubun; Munzir Munzir (Financial and Accounting Indonesian Research, 2024)
This purpose of this study is to determine whether Environmental,Social,and Governance (ESG) disclosure ha an influence on profitability (ROE). The sample in this study was 16 banking companies listed on the Indonesia Stock Exchange (BEI) obtained using the purposive sampling method and the security year was 2019 - 2022. The type of data used is secondary data in the form of financial reports,annual reports and sustainability reports. The results of this 1). Environmental disclosure has a negative and insignificant effect on the profitability of banking companies listed on the IDX. This result means that environmental disclosure has not become a determining factor in influencing the profitability of banking companies. 2). Social disclosure has a negative and insignificant effect on the profitability of banking companies listed on the IDX. This result means that social disclosure has not become a determining factor in influencing the profitability of banking companies. 3). Governance disclosure has a positive and insignificant effect on the profitability of banking companies listed on the IDX. This result means that governance disclosure has not become a determining factor in influencing the profitability of banking companies.